The role of digital leisure in family context with adolescents: A systematic review (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
This systematic review was carried out to provide information about the role of digital leisure in family relationships with adolescent. After conducting a search in the main databases, we present the findings of 14 articles from 2008 to 2020. Nine included articles used quantitative methodology and were theoretically based on bidirectional socialization and bottom-up technology transmission. The use of questionnaires is highlighted, and the most common sample size is parent-child dyads with adolescents in secondary education. This study evidence the importance of the role of digital leisure within the family context with adolescents and reveals a modification of family dynamics.